Buffer zones in Latin America: comparative analysis of legal frameworks on sanctions for alteration of the environment and landscape - Vásquez Sánchez, José Ronald (2023)
The objective of this investigation is to analyze the legal treatment of buffer zones in Peru and other Latin American countries, focusing mainly on contrasting the administrative and criminal sanctions that could be established due to the alteration of the environment and landscape through the building or construction of works in this area, to identify shortcomings, gaps and opportunities to improve the existing regulation. The study corresponds to a type of applied research with the design of fundamental theory, which involved carrying out a detailed and systematic review of the laws of different Latin American countries such as Peru, Brazil, Ecuador, Bolivia and Colombia. The documentary analysis guides were divided into three guidelines, the general regulation of buffer zones, administrative sanctions and criminal sanctions generated by the indicated conduct. Among the results obtained, we find that all countries regulate protection measures for buffer zones, likewise, Colombia, Brazil and Ecuador explicitly establish that construction in buffer zones without authorization constitutes an administrative offense, while in the case of Bolivia and Peru, will depend on what is established in their management plans, and only Peru, Brazil and Colombia classify it as a crime.